Mathematics Students’ Satisfaction In Carrying Out Online Thesis Advisory During The Covid-19 Pandemic at IAIN Bukittinggi - M. Imamuddin; Isnaniah; Zaharuddin M; Weti Susanti; Andryadi; Zulmuqim; Syafruddin Nurdin (CV. AFDIFAL MAJU BERKAH, 2022)
During the COVID-19 pandemic, a thesis advisory was carried out online. Further, online thesis advisory has motivated students to immediately complete their thesis even though the student lives in a different place from the supervisor. This study aimed to describe students’ satisfaction in carrying out online thesis guidance. The subjects of the study were 40 students. The instrument used was in the form of a questionnaire distributed via a google form. Besides, the data analysis used was a descriptive data analysis using formulas and student satisfaction tables. The results of this study; 1) The guidance of the supervisor in thesis advisory obtained a final score indicating an average of 80.6. 2) The thesis advisory is given by the supervisor also indicated a very good assessment with the acquisition of a score of 87.3, and 3) Very good assessment was also given by students towards facilities available indicating an average score of 75.7. In conclusion, students who carried out the online thesis advisory process were very satisfied with its process